ANALISYS OF THE INFLUENCE OF GLUE JOINTS ON THE MEASUREMENT OF PHYSICAL PROPERTIES OF STRUCTURAL ELEMENTS USING FIBER BRAGG GRATING - Tomasz Zieliński; Łukasz Zychowicz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2020)
The research presents the analysis of the influence of the glue connection on the measurement of elongation of stainless steel and aluminum samples by means of fiber Bragg grating (FBG) with uniform fibers used as a measuring transducer. Research indicates two possible factors affecting the deformation of the transmission spectrum obtained during elongation measurement. One of them is the type of adhesive that is used to make the connection between the fiber Bragg grating and the tested sample. The second possible factor is method of connection's execution. The need for research on glue connection resulted from the formation of defects mainly in the form of numerous side bands visible in the transmission spectrum during the measurement of elongations. The test results were presented in the form of graphs obtained on the basis of transmission characteristic.